2017
DOI: 10.1088/1751-8121/aa5fb6
|View full text |Cite
|
Sign up to set email alerts
|

Spin-1/2 sub-dynamics nested in the quantum dynamics of two coupled qutrits

Abstract: In this paper we investigate the quantum dynamics of two spin-1 systems, S 1 and S 2 , adopting a generalized ( S 1 + S 2 ) 2 -nonconserving Heisenberg model. We show that, due to its symmetry property, the nine-dimensional dynamics of the two qutrits exactly decouples into the direct sum of two sub-dynamics living in two orthogonal four-and five-dimensional subspaces. Such a reduction is further strengthened by our central result consisting in the fact that in the four-dimensional dynamically invariant subspa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…III C, exhibits a constant maximum level of entanglement (1/2) during the evolution. Such a peculiar feature is independent of the specific time-dependence of the field and it may be understood at the light of the analysis reported in 53 . There the authors analyse the same two-qutrit model but with time-independent fields.…”
Section: A Four-dimensional Sub-dynamicsmentioning
confidence: 68%
See 3 more Smart Citations
“…III C, exhibits a constant maximum level of entanglement (1/2) during the evolution. Such a peculiar feature is independent of the specific time-dependence of the field and it may be understood at the light of the analysis reported in 53 . There the authors analyse the same two-qutrit model but with time-independent fields.…”
Section: A Four-dimensional Sub-dynamicsmentioning
confidence: 68%
“…In Ref. 53 it was shown that two dynamically invariant Hilbert subspaces exist: one of dimension four spanned by {|10 , |01 , |0 − 1 , |−10 } and the other one of dimension five spanned by {|11 , |1 − 1 , |00 , |−11 , |−1 − 1 }. They are related to the two eigenvalues (±1) of the constant of mo-tionK = cos(πΣ z tot ),…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…[42], which, besides having been already applied to treat timedependent spin Hamiltonian models beyond the relatively simpler s = 1/2 case [46,48,49], has even the merit of offering tools to solve a wide class of special DREs not considered in the specialized literature so far.…”
Section: Conclusive Remarksmentioning
confidence: 99%